Analisis Aktivitas Wisatawan dan Dampaknya Terhadap Ekonomi Lokal di Kawasan Pantai Seminyak - Aura Bebyna; Shafa Yuniar Putri Rosyadah; Nabiilah Putri Syahrani; Afifah Wardah Ariesty; Muhammad Altru Diyas; Sugiantoro; Nurul Hasanah (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze tourist activities and their impact on the local economy in the Seminyak Beach area of Bali, a prominent tourist destination experiencing rapid growth. Using a qualitative approach, data were gathered through in-depth interviews, participatory observation, and literature review. The findings reveal a wide range of tourist activities, including sunbathing, surfing, enjoying local culinary experiences, nightlife, and shopping for local products. International tourists tend to engage in nature-based and relaxation activities, while domestic tourists show stronger interest in consumption-driven activities such as souvenir shopping and photo documentation. These activities stimulate the growth of Micro, Small, and Medium Enterprises (MSMEs), generate employment, and enhance demand for local goods and services. However, this growth also presents challenges such as rising living costs, risk of gentrification, and economic vulnerability due to over-dependence on tourism. Therefore, sustainable development strategies are needed, including MSME digitalization, strengthening community-based tourism (CBT), social media promotion, and infrastructure enhancement.